A physical-cognitive intervention to enhance gait speed in older mexican adults - Salazar González, Bertha Cecilia; Cruz Quevedo, Juana Edith; Gallegos Cabriales, Esther Carlota; Villarreal Reyna, María de los Ángeles; Ceballos Gurrola, Oswaldo; Hernández Cortés, Perla Lizeth; Garza Elizondo, María Eugenia; Gómez Meza, Marco Vinicio; Enríquez Reyna, María Cristina (2014)
Purpose: To test the effects of a physical-cognitive exercise intervention on gait parameters under dualtask conditions in community-dwelling older adults. Design. A repeated-measures quasi-experimental design, with control and exercise groups, was used. Setting. Study participants consist of a convenience sample recruited from senior citizens’ centers in Monterrey, Mexico. Subjects: A total of 143 sedentary participants ages 65 to 92 years per group participated. Intervention. A combined 45- to 60-minute program of physical and cognitive exercises was conducted in three weekly sessions during 12 weeks for the exercise group. Measures. The spatial gait parameters of speed (cm/s), step width, and stride length (cm); and the temporal parameters of single and double support time, cadence (steps per minute), and swing time (s) were measured using the GaitRite. Counting backwards or naming animals represented cognitive performance. Analysis. Two (groups: exercise group vs. control group) by three (time: baseline, week 6, and week 12) repeated-measures multivariate analysis of variance (MANOVA) was applied. Results: Repeated-measures multivariate analysis of variance revealed a significant group effect (Wilks lambda F4,279¼6.78, p , .001); univariate analysis showed significant differences for gait speed (m/s), stride length, cadence, step width, and double support time. Time-by-group interaction showed significance in gait speed and stride length. Conclusion: The exercise group participants showed increased gait speed, cadence, and stride length, and reduced their step width and time spent with both feet on the ground. Walking while simultaneously performing a cognitive task might prepare older adults for competing/interfering demands from their environments. The protective health benefits of this intervention remain to be investigated.